Distribution of Cellulase Activities in Acetes Shrimps Living in the Matang Mangrove Forest Reserve, Malaysia - Tanimura, Aya; Niiyama, Takatoshi; Hanamura, Yukio; Okutsu, Tomoyuki; Toyohara, Haruhiko; Tanaka, Katsuhisa; Man, Alias (Malaysian Journal of Science, 2013)
For the purpose of investigating the cellulose degradation mechanism in mangrove estuaries, cellulase activities of three Acetes shrimps (Acetes sibogae, A. japonicus and A. indicus) were examined in the Matang Mangrove Forest Reserve (MMFR). As a result of cellulose plate assay measurement, we detected the activities from all three species. SDS-PAGE zymographic analysis revealed that all Acetes shrimps demonstrated active bands at approximately 25 kDa and higher than 100 kDa. In addition, by quantifi cation of reducing sugar production, hepatopancreas samples of Acetes showed signifi cantly higher cellulase activity compared to whole body samples suggesting their endogenous origin. Our fi ndings that cellulase activities are widely distributed among the Acetes shrimps living in the MMFR, suggests that mangroves are indirectly utilized by higher trophic consumers. (Keywords: cellulase, mangrove, Acetes, hepatopancreas)